Penerapan Metode ELECTRE II Dalam Menentukan Faktor Yang Mempengaruhi Prestasi Belajar Mahasiswa Untuk Meningkatkan Nilai IPK - Nurinda Utari Damanik; Poningsih P; Irawan I (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2020)
One of the goals of the teaching and learning process is changes in behavior both aspects of knowledge (cognitive), attitude (effective),and psychomotor aspects. Learning achievement achieved by students is essentialy a reflection of learning efforts. In general,the better the learning effort, the better the achievement will be,of course this is inseparable from the factor that influnce it, among others, motivation of parents’ level of education, ways of learning taught by lecturers, concentration. Hower most students lack learning achievement so the IPK value decreases. Whereas if the IPK is high the it will be very easy to determine the job. Student learning achievement and to increase the IPK is strongly influenced by a factor for that it requires a study to increase the value of I. Realizedby making a decision support system in determining the factors that influence student achievement to increase the IPK score.